Development of Teaching Materials Based on The Discovery Learning Model Using Canva for Descriptive Text Writing - Tessa Pramesti; Elfia Sukma; Adrias Adrias; Desyandri Desyandri (Journal of Educational Sciences, 2026)
This study aims to develop teaching materials based on the Discovery Learning model using Canva to improve descriptive text writing skills of elementary school students. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Data were collected through validation sheets, questionnaires, interviews, and tests, and analyzed using descriptive quantitative and qualitative techniques The novelty of this study lies in the integration of Discovery Learning and Canva-based digital teaching materials to support visually interactive and student-centered descriptive writing instruction in elementary schools. The results showed that the developed teaching materials met the criteria of validity, practicality, and effectiveness. The average validation score increased from 78.37% (valid) to 92.30% (very valid). Practicality results indicated an average score of 93.00% (very practical) from teachers and students. Effectiveness was evidenced by an increase in students’ average scores from 62.40 (pretest) to 84.70 (posttest), with an N-Gain value of 0.59 (moderate category). These findings indicate that the integration of Discovery Learning and Canva-based materials enhances student engagement, motivation, and writing skills. Therefore, the developed teaching materials are feasible and effective for improving the quality of Indonesian language learning in elementary schools.